Pengaruh Penggunaan Media Sosial dalam Pembelajaran terhadap Prestasi Belajar Siswa - Sri Wahyuni Juika; Syamsu A Kamaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of social media use in learning on student achievement. In today's digital era, social media such as WhatsApp, YouTube, Instagram, and TikTok function not only as a means of communication but also as a supporting medium for the learning process. This study used a quantitative descriptive approach with a survey method among high school students. Data were collected through a questionnaire regarding the intensity, purpose, and method of social media use in learning activities. The results indicate that targeted and proportional use of social media has a positive influence on increasing student learning motivation, understanding of the material, and academic achievement. However, excessive, unsupervised use of social media can negatively impact concentration and learning discipline. Thus, social media has great potential as an innovative learning tool if used wisely and in accordance with educational needs. Keywords: social media, digital learning, learning achievement, students, education